A4.6 TGF-β is a potent inducer of nerve growth factor in articular cartilage via the ALK5-SMAD2/3 pathway. Potential role in OA related pain?. (13th February 2015) - Davidson, EN Blaney; van Caam, APM; Vitters, EL; Bennink, MB; Thijssen, E; van den Berg, WB; Koenders, MI; van Lent, PLEM; van de Loo, FAJ; van der Kraan, PM
Abstract : Background and objectives: Pain is the main problem for patients with OA. Pain is linked to inflammation, but in OA a subset of patients suffer from pain without inflammation, indicating an alternative source of pain. NGF inhibition very efficiently blocks pain during OA, but the exact source of NGF is unclear. NGF is elevated in animal models of OA with cartilage damage without inflammation. TGF-beta is released from cartilage upon damage. We investigated whether TGF-beta could contribute to NGF expression in the joint and which signalling route is involved. Materials and methods: Murine and human chondrocyte cell lines, primary bovine and human chondrocytes, and cartilage explants from bovine metacarpal joints and human OA joints were stimulated with TGF-β1 and/or IL-1β as a positive control for NGF induction. We analysed NGF expression on mRNA level with QPCR and stained human OA cartilage for NGF immunohistochemically. Cultures were additionally pre-incubated with inhibitors for TAK1 (oxozeaenol), Smad2/3 (SB-505124) or Smad1/5/8 (LDN-193189) signalling to identify the TGF-β pathway inducing NGF. Results: TGF-beta consistently induced NGF expression at higher levels than IL-1 in all of our experimental models: murine, bovine and human origin, in cell lines, primary chondrocytes and explant cultures. We initially expected TAK1 to be dominant and pivotal in NGF induction due to involvement in both IL-1 and TGF-beta signalling. TAK1 inhibition consistently reduced (but not blocked) TGF-β-induced NGF whereas it fully blocked IL-1β-induced NGF expression. In contrast, ALK5-Smad2/3 inhibition fully blocked TGF-β-induced NGF expression. Blocking the Smad1/5/8 pathway did not affect NGF expression. Human OA primary chondrocytes had a large variation in basal NGF levels (mRNA and histology). TGF-β consistently induced a higher level of NGF induction than IL-1 in these chondrocytes despite variable basal levels of NGF when stimulating human OA cartilage explants with TGF-beta, NGF expression increased, which could be fully blocked by inhibiting ALK5-Smad2/3 signalling. Conclusions: This is the first time that it is shown that TGF-β induces NGF expression in (primary) chondrocytes. Moreover, we found that TGF-beta consistently induced NGF at higher levels than IL-1. In addition, IL-1-induced NGF could be fully abrogated by TAK1 inhibition, but this only reduced TGF-beta-induced NGF expression. In contrast blocking signalling via ALK5-Smad2/3 fully abrogated the TGF-beta-induced NGF expression. Clearly, our data show that there are sources of NGF other than inflammation in the joint and that this should be taken into account when studying pain in OA.